Of the Trivial and the Radical: Is There a Coherent Constructivist Pedagogy? - Cato, Dennis (Paideusis, 2006)
Where a pedagogy is to be understood not simply in its weak sense as a range of classroom techniques but rather in its strong sense as embodying some conception of the ends of education such techniques subserve, coherence derives from the theoretical basis to which that pedagogy appeals. Where, however, such a theoretical basis is indistinguishable from that it purports to supplant or where it is inherently self-contradictory, the resulting pedagogy is incoherent. It is maintained here that “trivial constructivism” fails in the first respect and “radical constructivism” in the second and that any pedagogies based upon them are therefore incoherent.